Adsorption of some toxic elements from water samples on modified activated carbon, activated carbon and red soil using neutron activation analysis - Mohd Yusof, Alias; Rahman, Md. Mokhlesur; Wood, Abdul Khalid (SpringerLink, 2007)
A simple and sensitive method for the determination of some metalloids and heavy metals in water samples is presented. The method is based on the preconcentration of the attachment of chelating functionalities with metalloids and toxic metals irreversibly and targeted towards toxic metals adsorbed on modified activated carbon, activated carbon and red soil particles at pH 3.0–9.0±0.2, followed by quantitative determination using instrumental neutron activation analysis (INAA), on the absorbers. Attachment results from attraction that may be physical, chemical, electrical, or a combination of all three. The efficient removal of metalloids and toxic metals, especially arsenic, chromium and mercury is anticipated. The adsorption capacity of the chemically modified activated carbon materials was evaluated for the above mentioned metalloid and toxic metal ions in the presence of iron ions and simulated water samples. Red soil particles containing iron was utilized in the control of oxidation-reduction reaction with metalloids and toxic metals. The preconcentration of the elements of interest on red soil particles, activated carbon and modified activated carbon at different depths, pH and oxidation states was investigated. The results obtained showed good agreement with certified values giving relative errors of less than 10%.